FACTORS INFLUENCING SATISFACTION OF ENTERPRISES WHEN USING E-TAX PAYMENT SERVICES AT TAX DEPARTMENT OF TRANG BOM DISTRICT, DONG NAI PROVINCE - Dinh Hai, Le; Thi Lan Huong, Mai; Thi Kim Phung, Le (Journal of Forestry Science and Technology, 2020)
Electronic tax payment services have brought many benefits to taxpayers including saving in both time and costs, but in order for this service to be replicated and more effective, it is necessary to have assessments of taxpayers, especially enterprises, on the quality of this service. This article attempts to examine the factors that significantly influence satisfaction of enterprises when using e-tax payment services at tax department of Trang Bom district, Dong Nai province. Based on the primary data gathered from surveying 200 enterprises (including: joint stock companies, limited liability companies, private enterprises...) at tax department of Trang Bom district, Dong Nai province, through exploratory factor analysis (EFA), and multiple linear regression, the findings of this study show that reliability, efficiency, website design, and charge/fee are the most influential factors to satisfaction of enterprises when using e-tax payment services at tax department of Trang Bom district, Dong Nai province. The research results can be a good reference for the tax department of Trang Bom district, Dong Nai province in particular and the taxation industry in general in improving quality of electronic tax services, as well as improving efficiency in the reform and modernization of the tax industry in the coming time.